Epistemological Foundations of Science and Technology in Islam: A Literature Review - Syarip Syarip; Zuhdiyah Zuhdiyah; Maryamah Maryamah (Academia Open, 2026)
General Background: Epistemology constitutes a foundational dimension in the construction, validation, and transmission of scientific knowledge, shaping research methodologies, educational paradigms, and ethical orientations across disciplines. Specific Background: Within Islamic intellectual tradition, epistemology integrates revelation, reason, and spiritual insight, historically contributing to global knowledge development, particularly during the Abbasid era through translation, synthesis, and scientific inquiry. Knowledge Gap: Despite extensive historical contributions, systematic articulation of how Islamic epistemological models relate to contemporary science and technology remains underexplored in modern academic discourse. Aims: This study examines the epistemological foundations of knowledge and technology in Islam through a qualitative library-based analysis of classical and contemporary sources. Results: The findings demonstrate that Islamic epistemology is structured around authoritative sources and three complementary modes of knowing—bayānī, burhānī, and ʿirfānī—forming an integrated framework that guides scientific reasoning, educational curricula, and ethical considerations. Novelty: The study consolidates diverse Islamic epistemic principles into a coherent analytical model that positions Islamic epistemology as a holistic alternative to dominant empirical paradigms. Implications: This integrated framework offers a conceptual basis for aligning modern scientific and technological development with moral and spiritual values, supporting ethically grounded scholarship and sustainable intellectual engagement with modernity. Highlights: Islamic knowledge construction is grounded in an integrated system combining textual authority, rational inquiry, and spiritual insight. Historical Islamic scholarship provided foundational structures for global scientific development through synthesis and translation. Contemporary scientific discourse can be situated within an Islamic moral and epistemic framework without abandoning rigor. Keywords: Islamic Epistemology, Science and Technology, Philosophy of Science, Islamic Education, Knowledge Systems